Do Verdão à Arena Pantanal : tramas identitárias nas ocorrências culturais e arquitetônicas do futebol mato-grossense - Lima, Fabiana Cristina de (2019)
The thesis presented reflects a doctoral research in Contemporary Culture Studies of PPGECCO/UFMT, with the general objective of verifying the significance attributed by football sports agents to the Governador José Fragelli Stadium - Verdão and the Arena Pantanal, as a way of understanding the general occurrences in the main spaces of play that influence the formation of the local football identity. The qualitative research method led to the investigation and the semi-structured interview was used as instruments of data collection with twelve football players, with mean age of fifty-five years, who were questioned in the period between June and November of 2018. The analysis of the data followed the suggested procedures for understanding the essence of what was intended to be verified, and this allowed the elaboration of four categories of results: "From mato-grossense football in full growth, Verdão is born", "From glory times to decadence: the trajectory of mato-grossense football between the 1970 and 2018", "The World Cup is ours! From a seasonal motivation arises the Arena Pantanal" and "The architectural structure and the relation of familiarity with the space of game: The Verdão and the Arena Pantanal constituted in the football scene mato-grossense". These categories allowed the verification of the meanings attributed by the research participants to Verdão Stadium and Arena Pantanal, and also allowed the understanding of how the identification process occurred with the old and the new “big house” of football mato-grossense. The information provided by the sports agents participating in this investigation proved to be skillful in the outline of the relations established between the Verdão Stadium and the Arena Pantanal for mato-grossense football, which allowed the following points to be established: 1 – the local football game, today, it represents less than it used to be; 2 – the fans, asset, now feel mere spectators active; 3 - there is still a very intense affective relationship with the Stadium José Fragelli - Verdão, extremely active on the memory of the subjects interviewed and 4 – although Mato Grosso football teams do not demonstrate conditions to add audiences in the state's new sports equipment, Arena Pantanal has an identity relationship with one of the current teams, due to the positive experiences he is already able to perform in it. Thus, we consider that the construction of the Governador José Fragelli Stadium - Verdão meant the construction of the identity references of a more modern, organized and powerful football in the state of Mato Grosso and that the Arena Pantanal has not yet been able to establish itself as an identity place for traditional sportsmen in the state.